Jogos de linguagem matemáticos da comunidade remanescente de quilombos da Agrovila de Espera, Município de Alcântara, Maranhão - Castro, Raimundo Santos de (2016)
[EN]This research aimed to understand what is manifest in the mathematical practices of members of the remaining community of quilombos of Agrovila Espera, Alcântara - MA, in their everyday social practices, questioning them from their not universal and decoding the effects of significance and meaning assigned to them by community members. The study that led to this text was developed through a qualitative research of ethnographic and analyzes were assisted by ethnographic microanalysis with the support of elements of philosophical thought of Ludwig Wittgenstein. Part initially of theorizing of what became known as “early Wittgenstein” to forward understandings about the notions of “Wittgenstein”, in particular the language of games, trying to present contributions to research in mathematics education that apply to the Ethnomathematics. The leading practice was to manufacture and “empaneiramento” of cassava flour and observations and interviews with audio recordings and video, helped in understanding the dynamics of social relations that are established in the community who have the mathematical practice their sense of existence. It is emphasized that the intertwining of Wittgenstein's notions with the speeches of individuals, allowed also to understand how the mathematical language games that make up and characterize such practices and that remain in its different uses, collaborate for the development of their social practices relating to work and livelihood. The made bibliographic studies and research developed ethnographic allowed further understand that since the 1980s, when the start of dispossession, displacement and resettlement for the implementation of the Alcantara Launch Center (CLA), there is the systematic loss of traditions and socio-cultural aspects of these people and, among them, their mathematical practices. Compulsory changes in their lives, also caused changes in their ways of relating to other communities and interrelate with their own members by changing their historical social practices.